Chemicals Analysis of Drilled Ground Waters in Moa Island, Maluku, Indonesia - Putra, M. Sulthon Nurharmansyah; Hermana, Nabila Swarna Puspa; Sumarno, Ari Pitoyo (Indonesian Journal of Chemical Studies, 2023)
Moa Island is one of the remote Indonesian Islands that face the difficulty in accessing clean water, especially during the dry season. One way to get clean water is by drilling for groundwater. The drilled groundwater in Kaiwatu Village on Moa Island, Southwest Maluku Regency, Maluku Province, was analyzed for its content to obtain primary data. Primary data related to the quality of drilled groundwater sources includes chemical, physical, and microbiological parameters. The results of chemical parameters obtained from the test results were <0.01 mg/L fluoride, total chromium, nitrite, nitrate, iron, manganese, zinc, cyanide, lead, <0,001 mg/L cadmium, 17.9 mg/L hardness, sulfate 147.55 mg/L, pH 7.50, and organic substances 2.8 mg/L.  The physical parameter analysis showed a turbidity level of 3.71 NTU, a temperature of 26.8 °C, and a color of 5 TCU. The microbiological parameters obtained by the analysis were 0/100 mL. Primary data was then compared with secondary data, namely environmental health quality standards and air health requirements from Minister of Health Regulation No. 32 of 2017 for chemical and physical parameters, as well as water quality requirements and monitoring from Minister of Health Regulation 416/MENKES/IX/1990 for microbiological parameters. The analysis results using a comparison of primary and secondary data showed that all parameters contained in the primary data had values below the safe limits set by the requirements in the secondary data.